The Impact of Per Capita GRDP, Inflation, Unemployment, and Food Prices on Food Security in Banyumas Regency During The Covid-19 Pandemic - M. Aris Pujiyanto; Muhamad Solekan; Dwi Putriana N Kinding (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2025)
This study aims to determine the influence of economic factors on food security in Banyumas Regency during the COVID-19 pandemic. The pandemic has intensified vulnerabilities in Banyumas, where economic challenges, such as declining GRDP per capita, rising unemployment, and fluctuating food prices, have heightened the risk of food insecurity. As a region reliant on agriculture and local markets, Banyumas struggles to maintain food accessibility and affordability amid disrupted supply chains and reduced income levels. The research uses a descriptive analytical approach, utilizing secondary data from official reports, economic surveys, and government databases. Economic variables such as GRDP per capita, inflation, unemployment rate, and food prices are examined using a multiple linear regression model to assess their influence on food security. The analysis revealed that GRDP per capita (p = .037), unemployment rate (p = .007), and the pandemic (p = .003) significantly affect food security, while inflation approaches significance (p = .065). Interestingly, the price of staple foods, like medium rice, shows no statistically significant effect (p = .875), suggesting stabilizing measures, such as subsidies or price controls, may mitigate price volatility. With an adjusted R-squared value of 0.922, the model demonstrates strong explanatory power. The findings highlight that GRDP per capita and unemployment rates critically influence food security in the region. The study recommends that the government prioritize improving food accessibility and availability by enhancing local food production, expanding distribution channels, and bolstering food security networks.